2021
DOI: 10.1186/s12955-021-01813-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Global Impression of Change (CGI-C) and a Caregiver Global Impression of Change (CaGI-C) measure for ambulant individuals with Duchenne muscular dystrophy

Abstract: Background In clinical trials for rare diseases, such as Duchenne muscular dystrophy, clinical outcome assessments (COA) used to assess treatment benefit are often generic and may not be sensitive enough to detect change in specific patient populations. Thus, there is a need for disease specific COAs that track meaningful change among individuals. When developing such measures, input from clinicians, caregivers and patients is critical for assessing clinically relevant concepts and ensuring val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Assessment of adverse events (AEs), causality and cognitive and behavioral test results were subjective evaluations of study participants and were therefore not permitted to be conducted by the unblinded dispenser or administrator. Cognitive and behavioral tests included the Cambridge Neuropsychological Test Automated Battery (which measures brain function across 3 cognitive domains: visual memory, attention, and functional components of executive function), 25 the Brief Praxis Test (which screens for early features of dementia in adults with intellectual disability), 26 the Vineland II Adaptive Behavior Scales (which measure adaptive behaviors, including ability to cope with environmental changes, learn new skills, and dem-onstrate independence), 27 the Neuropsychiatric Inventory (which measures neuropsychiatric symptoms), 28 the Clinician Global Impression of Change (which measures symptom severity, treatment response, and treatment efficacy), 29 a global assessment of tolerability (performed by W.C.M., B.G.S., and A.D.B. ), and the Columbia-Suicide Severity Rating Scale (which measures suicidal ideation and behavior).…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of adverse events (AEs), causality and cognitive and behavioral test results were subjective evaluations of study participants and were therefore not permitted to be conducted by the unblinded dispenser or administrator. Cognitive and behavioral tests included the Cambridge Neuropsychological Test Automated Battery (which measures brain function across 3 cognitive domains: visual memory, attention, and functional components of executive function), 25 the Brief Praxis Test (which screens for early features of dementia in adults with intellectual disability), 26 the Vineland II Adaptive Behavior Scales (which measure adaptive behaviors, including ability to cope with environmental changes, learn new skills, and dem-onstrate independence), 27 the Neuropsychiatric Inventory (which measures neuropsychiatric symptoms), 28 the Clinician Global Impression of Change (which measures symptom severity, treatment response, and treatment efficacy), 29 a global assessment of tolerability (performed by W.C.M., B.G.S., and A.D.B. ), and the Columbia-Suicide Severity Rating Scale (which measures suicidal ideation and behavior).…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent study of Lilien et al [ 54 ] explored the digital biomarker in home-based monitoring using a wearable magneto-inertial sensor (VMIS) for 23 ambulant DMD patients. The study demonstrated that the device’s variables were correlated with the clinical validated scores and are sensitive to change in the DMD patients over 6 months, thus providing objective and reliable data.…”
Section: Towards New Therapies: Proof Of Concept Of Trial Readiness A...mentioning
confidence: 99%
“…Corticosteroids are the most common supportive treatment for DMD and are able to delay the loss of ambulation and may reduce the likelihood of needing spinal surgery to treat scoliosis [ 5 , 14 , 15 ]. More recently, exon-skipping treatments for patients with specific genotypes have been shown to attenuate pulmonary and ambulatory decline compared with mutation-matched natural history controls; however, only a small portion of the overall patient population (approximately 30%) can benefit from these advancements [ 16 – 22 ]. Emerging molecular and gene therapies designed to treat underlying disease process across the spectrum of possible genotypes in DMD are expected to change future DMD management [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a handful of qualitative studies have described the symptoms and impacts of DMD on patients [ 22 , 24 26 ]. These studies were limited to ambulatory boys and included relatively small sample sizes (< 10 patients and/or caregivers).…”
Section: Introductionmentioning
confidence: 99%